New business models for sustainable spare parts logistics: A case study. - González-Varona, José Manuel; Poza García, David; Acebes Senovilla, Fernando; Villafáñez Cardeñoso, Félix Antonio; Pajares Gutiérrez, Javier; López-Paredes, Adolfo (MDPI, 2020)
Additive manufacturing of spare parts significantly impacts industrial, social, and environmental aspects. However, a literature review shows that: (i) academic papers on the adoption of additive manufacturing have focused mainly on large companies; (ii) the methods required by SMEs to adopt new technologies differ from those employed by large companies; and (iii) recent studies suggest that a suitable way to help small- and medium-sized enterprises (SMEs) to adopt new additive manufacturing technologies from the academic world is by presenting case studies in which SMEs are involved. Given the increasing number of global SMEs (i.e., SMEs that manufacture locally and sell globally), we claim that these companies need to be assisted in adopting spare-parts additive manufacturing for the sake of resource and environmental sustainability. To bridge this gap, the purpose of this article is to present a case study approach that shows how a digital supply chain for spare parts has the potential to bring about changes in business models with significant benefits for both global SMEs (more effective logistic management), customers (response time), and the environment (reduced energy, emissions, raw materials, and waste).
Keywords: Impresión 3D; Abastecimiento; Pequeñas y medianas empresas; Negocios - Gestión; Resource efficiency; Digital supply chain; Spare parts; Additive manufacturing; Small- and medium-sized enterprises (SMEs); Business model; On-demand production